Formacja moralna. Wymiar etyczny i chrześcijański - Bastianel, Sergio (Horyzonty Wychowania, 2017)
The accent put by the Second Vatican Council on the „enormity of vocation of those who believe in Christ” and trust in the ability to recognize and take on the requirement to „bring fruit of love, which values the world’s life” as a „duty”, confirms and encourages to a new way of understanding the formation of consciousness. Furthermore, understood in this way, the conciliar authority adopts the shape of a great provocation in contemporary world and in relation to the conditions we live in as Christians. The multitude of ethical proposals, frequent existential break and spiritual loss, which put the unity and aim in human life in jeopardy, remind, in some aspects, (perhaps emphasizing the issue) of the situation of enslavement, not much diverging from the one in which our fathers lived in lavish Egypt, or, a little bit later, in exile. In the face of the appearing situation, namely the scattered personal dimension of life, not infrequently subject to the dominance of objects, circumstances, or arbitrariness of various circles, where the external outweighs the internal life, a call for convincing and bolstering up courage to return to rules is sometimes heard. In this context, a definite conciliar stand on this issue, in particular induces to reflection, since instead of putting emphasis on quoting the rules, it calls us to adopt a position of critical consciousness and an equally critical concern for our internal life.